COMPUTER ANXIETY DALAM KONTEKS PENDIDIKAN AKUNTANSI - Dodik Ariyanto; Ayu Aryista Dewi; I Made Sukartha (Modus, 2017)
AbstractThe development of information technology in the era of modernization and globalization impact on the world of accounting, which is now integrated with the computer. Accounting student is required to use and operate computers and accounting software given the importance of mastering computer technology and telecommunications in the business world. The problem arises when there are still students who react negatively ranging from passive response to the rejection of the use of computers. This study tried to delve deeply into the influence of personality type, gender, and GPA to anxiety computing (computer anxiety) in the context of accounting education.Research using instruments Computer Anxiety Rating Scale (CARS) to measure anxiety variable computing and instruments Myers Briggs Type Indicator (MBTI) to measure variables personality type.Samplingusing 180 students in Faculty of Economics and Business Udayana University majoring in accounting. The data collected using the method of survey with questionnaire technique.Regression analysis is used as the data analysis technique with SPSS.The result that responden with extrovert type, high-relative GPA, tend to have a lower level of computer anxiety. However, the difference of gender does not have any variant in computer anxiety level.